Assessing impact of chemical compatibility of additives used in asphalt binders: A case study using plastics. (12th December 2022) - Sreeram, Anand; Filonzi, Angelo; Komaragiri, Satyavati; Lakshmi Roja, K.; Masad, Eyad; Bhasin, Amit
Abstract: Economic and environmental factors mandate the use of engineered materials as well other waste or industrial by-products as an additive or extender in asphalt binders and mixtures. In most cases, the impact of these materials on the long-term performance of asphalt binders and concomitant mixtures is evaluated on an ad hoc basis. This study explores the use of chemical compatibility based on the Hansen Solubility Parameters (HSP) to better understand and predict the performance of modified asphalt binder blends. Specifically, this approach is applied to the case of plastic materials that are increasingly being evaluated as a value-added extender for binders. In order to investigate the role of chemical compatibility on the macroscopic performance of such modified blends, two different types of polyethylene (PE) plastics with varied compositional characteristics were studied, referred to as PE-1 and PE-2. Additionally, the impact of using elastomeric polymers as co-modifiers with plastics were also examined. From a solubility perspective, the results indicated that PE-1 and asphalt binders show reasonable compatibility, whereas PE-2 was incompatible. Further analyses were conducted to correlate these results using microscopic and rheological tools. PE-1 modified binders were seen to be well dispersed in the binder matrix and had acceptable performance, particularly with the combined use of co-modifiers. On the other hand, all PE-2 modified binders showed poor dispersion and consequently inferior rheological performance. The results also indicated that the addition of co-modifiers will only improve the compatibility of plastics in blends on a selective basis. Overall, the work conducted in this study demonstrates the impact of chemical compatibility on the macroscopic performance of different plastic modified blends. The approach used in this study can also be extended for use with other additives used in asphalt binders to better understand the chemo-mechanics of the different additive-binder blends and impact on performance. Highlights: The use of Hansen solubility parameters (HSP) to examine the material compatibility between plastics and asphalt binder. Fundamental chemical compatibility of plastics with binder changes based on composition. Decreased levels of compatibility associated with poor rheological performance. Closer examination of plastics required to design high quality mixes.